The transparency of published health technology assessment-based recommendations on pharmaceutical reimbursement in Poland. (4th July 2017) - Bochenek, Tomasz; Kocot, Ewa; Rodzinka, Marcin; Godman, Brian; Maciejewska, Katarzyna; Kamal, Susan; Pilc, Andrzej
ABSTRACT: Background: The appropriate access to public information is very important for healthcare system stakeholders. The goal of this study was to examine how the execution of the formally existing right to public information on the HTA-based recommendations on reimbursement of new health technologies from public funds has been changing in Poland. Methods: All recommendations published within two predefined equal periods of time between 2013 and 2015 were analyzed. The gathered data was subjected to statistical analysis. Results: The frequency and intensity of censoring the published HTA-based recommendations on the pharmaceutical reimbursement has diminished. The text readability and clarity of message has improved, although the degree of decisiveness of the recommendations has dropped. Conclusion: The positive changes in the public communication policy should be continued. The transparency of the HTA-based recommendations should be increased further in some areas in the future.